WIRELESS WATER METER USING ANDROID APPLICATION - Kasturi, Muhammad Hazwan (IRC, 2019)
Water meter has been implanted in numerous parts of the world for utilization. It is used by water organization to check the amount of water used. In Malaysia, the procedure to collect the data is by going to premise every month. The monthly bill is then being calculated by referring to the endorsed rate given in every district. The step taken is very slow. Hence, the solution is to build a new water meter system. The system consists of few processes where collected data can be checked via mobile application. The system has many advantages to the consumer. The process to get liquid flow is given by the result of cross-sectional region of the pipe and the average velocity of the flow. The procedure that has done is elaborated in this report. It includes on deciding the design and choosing the right material and component for the project. Lastly, the report contains recommendation that can be made for future works.